Mentoring for Pre-University Principals: Array - Botez, Gina Lacramioara; Curca, Mihaiela Cornelia (Didactica Danubiensis, 2022)
Naming school principals with a delegation, a situation very often seen in some counties, leads, in terms of school management, to instability and a so-calledtemporary situation.I believe that the current situation can be significantly improved if a mentoring program for pre-university principals is introduced into the system, in order to increase quality and performance.